Knowledge and Competency of First Aids and Basic Life Support (BLS) Skills in Speech and Hearing Students - Bhatarai, Prabuddha; Lokwani, Prateek; Bhattarai, Biraj; Paudel, Dilli Raj; Sharma, Aashish; Prabhu, Prashanth (Journal of Health and Allied Sciences NU, 2023)
Purpose This study aimed to analyze speech and hearing students' knowledge, awareness, and attitude regarding first aid and basic life support (BLS).Methods A descriptive cross-sectional survey study was performed through a web-based questionnaire regarding knowledge of first aid and BLS skills, experience, and views about training on these skills among speech and hearing students.Results Four-hundred forty-two students from 26 different speech and hearing colleges participated in the study. About 88.23% of participants reported the necessity of knowledge about BLS skills and first aids. Fifty-five percent of participants encountered at least one emergency during their training. There is significant difference between awareness and confidence in performing these skills (Mann–Whitney U test= 76.5; /z/= −2.39; p = 0.019; effect size = 0.27). Most of the students (92.5%) reported not being trained to perform first aid and BLS skills and seek inclusion of these skills in their academic curriculum.Conclusions Overall confidence in first aid skills is less in the students of speech and hearing when compared with the awareness level. Hence, formal training of first aid and BLS should be introduced into the curriculum to provide students with sound knowledge and practical skills and help them boost their confidence.
Keywords: first aid; basic life support; audiology; speech and hearing